2022
DOI: 10.3390/genes13122408
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inherited Copy Number Variation in ADAM3A and ADAM5 Pseudogenes with Oropharynx Cancer Risk and Outcome

Abstract: Inherited copy number variations (CNVs) can provide valuable information for cancer susceptibility and prognosis. However, their association with oropharynx squamous cell carcinoma (OPSCC) is still poorly studied. Using microarrays analysis, we identified three inherited CNVs associated with OPSCC risk, of which one was validated in 152 OPSCC patients and 155 controls and related to pseudogene-microRNA-mRNA interaction. Individuals with three or more copies of ADAM3A and ADAM5 pseudogenes (8p11.22 chromosome r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…TMB and MSI have emerged as major response-predictive biomarkers for the effectiveness of ICB therapy [ 24 , 25 ]. CNV, as a form of genomic structural variation, has been proven to be involved in the occurrence and development of various cancers and affects the prognosis of patients [ 37 , 38 ], and can also be used in cancer diagnosis [ 39 ]. As an epigenetic modification, DNA methylation often disrupts gene regulation and affects patient prognosis in a variety of cancers [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMB and MSI have emerged as major response-predictive biomarkers for the effectiveness of ICB therapy [ 24 , 25 ]. CNV, as a form of genomic structural variation, has been proven to be involved in the occurrence and development of various cancers and affects the prognosis of patients [ 37 , 38 ], and can also be used in cancer diagnosis [ 39 ]. As an epigenetic modification, DNA methylation often disrupts gene regulation and affects patient prognosis in a variety of cancers [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Carron et al, an increased risk of developing oropharynx squamous cell carcinoma was associated with the presence of three or more copies of the pseudogenes ADAM3A and ADAM5 [ 58 ]. The authors also identified a highly homologous region in the 3′-UTR sequence of ADAM5 and ADAM9 that serves as a binding site for miR-122b-5p.…”
Section: Pseudogenes As Functional Molecules In Cancermentioning
confidence: 99%
“…The authors also identified a highly homologous region in the 3′-UTR sequence of ADAM5 and ADAM9 that serves as a binding site for miR-122b-5p. The competition for this miRNA binding site between ADAM5 and ADAM9 suggests a potential mechanism for the coordination of their expression and the promotion of tumorigenesis [ 58 ].…”
Section: Pseudogenes As Functional Molecules In Cancermentioning
confidence: 99%
“…Smoking and drinking chronic habits [2] and HPV infection [3] are known risk factors for developing the disease. Additionally, inherited and acquired genetic alterations play important roles in pharynx cancer risk and progression [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%